Hubungan Aktivitas Fisik dengan Tingkat Kesakitan Warga Binaan Pemasyarakatan (WBP) di Lapas Perempuan Kelas II Pondok Bambu - Jihan Rahmawati; Trisiswati, Maya (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Research on the relationship between physical activity and morbidity levels of inmates, particularly in women's prisons, is still very limited. This study aims to provide empirical data that can be used as a basis for developing better physical training programs in women's prisons, while also supporting improvements in the quality of life of inmates and their readiness to return to society. This study used a quantitative design with a cross-sectional study approach. Activities carried out included data collection and measurement of the independent and dependent variables. This study analyzed variables related to the relationship between physical activity and morbidity levels among inmates at the Class II Pondok Bambu Women's Prison, East Jakarta. The results of the study showed (1) variations in the distribution of physical activity levels were relatively balanced between the low (34.6%), medium (33.3%), and high (32.1%) categories. (2) Morbidity rates in the sample indicated a significant burden of disease, the proportion of prisoners with low levels of morbidity was 39.7%, medium 24.4%, and high 35.9%. (3) Statistical analysis showed a significant relationship between physical activity levels and levels of morbidity in prisoners, the bivariate test (Chi-Square) produced p < 0.001, so the hypothesis that there is a relationship between physical activity and morbidity is accepted. (4) In an Islamic perspective, physical activity is believed to strengthen the body, prevent disease, and maintain physical and spiritual balance.